Spinal Stroke following Kidney Transplant. (21st May 2022) - Subramanian, Jayanthan B.; Siddiqui, Farjad; Chotai, Pranit N.; Al-Adwan, Yazan; Rajab, Amer; Washburn, Kenneth; Schenk, Austin D.; Limkemann, Ashley J.; Luttrull, Michael; Al-Ebrahim, Musab; Bumgardner, Ginny; Singh, Navdeep
Abstract : Complications are a part of surgery. Spinal infarctions are a dreaded complication of aortic surgery. We present a patient who developed a spinal infarct after a kidney transplant. We were unable to find a causative factor in our search for etiology. In our review of the literature, we were unable to find a similar report. We present this case report to highlight a rare complication of kidney transplantation and to reinforce that patients requiring kidney transplant are complex patients with multiple comorbidities that can cause a multitude of complications in the periop period.